Research on quality and performance of FRM laser welded joints with different shaft length ratios elliptical trajectory - Yang Zhang; Jieshi Chen; Wenshuai Zhang; Shanglei Yang; Zhengguo Yue; Jianwu Ding; Hao Lu; Kejin Zhang (Journal of Materials Research and Technology, 2023)
The emerging Flexible Ring Mode(FRM) laser technology has shown great potential for welding copper and its alloys with high reflectivity and has been widely used. The design of the welding trajectory significantly affects the porosity and performance of welded joints. This paper first selects the ellipse and its parameters from the three trajectories by numerical simulation method, then studies the appearance forming and counts the weld porosity through the longitudinal and cross-section developing quality, and finally uses a high-speed camera to monitor the copper Behavior of molten pool and spot oscillation process at the front of the plate. It is found that the trajectory of circular motion has a more stable heating process and has a preheating function for the center of the weld. Compared with linear welding, orbital welding achieves penetration of weld seam and forms better weld seam. Laser confocal tests show that S4(a1b0.5) has the most negligible variation in weld appearance and the best formability. S3(a0.5b0.5) has the lowest porosity, which also explains the mechanism of laser welding trajectory stirring the molten pool and pooling of pores under hydrostatic pressure. The tensile test shows that: S3 has the highest tensile strength (215.35 MPa), 89.79% of the base material. But its strain is only 50% of that of the S4 sample with almost the same tensile strength (215.03 MPa). Therefore, this paper proposes that an elliptical welding trajectory can be adopted to obtain welded joints with better tensile strength and plasticity, with the long axis along the welding direction and the short axis perpendicular to the welding direction. This study provides theoretical guidance for the optimal oscillation mode selection for tunable ring mode laser welding of highly reflective materials.